Electrical characterization and temperature reliability of 4H-SiC Schottky barrier diodes after Electron radiation. (February 2023) - Xiang, Meiju; Wang, Duowei; He, Mu; Rui, Guo; Ma, Yao; Zhu, Xuhao; Mei, Fan; Gong, Min; Li, Yun; Huang, Mingmin; Yang, Zhimei
Abstract: In this study, the operation of commercial SBD-based on 4H-SiC after radiation was assessed. The devices were subjected to electron radiation with an energy of 1.7 MeV at different fluences. Then the electrical characteristics of the devices were measured, and related parameters were calculated. The results show that the devices display good radiation resistance at the high fluence of 10 15 e/cm 2 . However, the performance of the devices degrade when the total fluence is 1 × 10 16 e/cm 2 . The variable temperature test and deep-level transient spectrum (DLTS) tests reveal the cause of performance degradation under high fluence. The variable temperature test result shows that the ideality factor of the device at 1 × 10 16 e/cm 2 increases compared with that devices, indicating more recombination centers are introduced. The donor concentration ( N D ) significantly decreases at 1 × 10 16 e/cm 2, and increases with increasing temperature in the range of 350–450 K. The DLTS results show that the change of N D with temperature is related to the decrease of Ec-0.91 defect concentration. During the variable temperature test, certain changes are found in the defects and the defects are due to the repair of the ionization damage during the heating process, the degeneration of the electrical characteristics is mainly caused by the ionization damage rather than the displacement damage. Finally, the radiation-induced displacement damage is mainly located in the region near the metal-semiconductor interface. Highlights: Four groups of SiC SBDs were subjected to electron irradiation experiments. The device exhibited good radiation resistance, and the electrical characteristics were severely damaged when the total fluence reached 1×10 16  e/cm 2 . Defects ET1, ET2, ET3, ET4 were introduced after radiation. The ET4 had a great deal to do with the degradation of electrical properties due to it closer to the center of the forbidden band and its capture cross section was larger. The capture cross section and the defect concentration increased and decreased, respectively, with the increase in temperature, indicating that temperature had a significant effect on the ND . The region where displacement damage exists was characterized and the result showed it was mainly located in the region near the interface.